In patients undergoing oesophagectomy does postoperative home enteral nutrition have any impact on nutritional status?. (5th May 2022) - Li, Xiaokun; Hu, Jianrong; Zhou, Jianfeng; Fang, Pinhao; Yuan, Yong
Summary: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was 'In patients undergoing oesophagectomy does postoperative home enteral nutrition have any impact on nutritional status?' Altogether, 50 articles were found using the reported search, of which 5 studies represented the best evidence to answer the clinical question. This consisted of 1 systematic review including a meta-analysis of 9 randomized controlled trials (RCTs), 3 RCTs and 1 cohort study. Main outcomes included loss of body weight and body mass index (BMI), change of serum albumin, haemoglobin, total protein and prealbumin, rates of nutritional risk patients and score value of patient-generated subjective global assessment. The meta-analysis concluded that there were significant differences in the loss of body weight and BMI between 2 groups, with higher values observed in the HEN group than that in the control group. One RCT showed that patients receiving HEN had a significantly lower weight loss compared with the control group. However, in another RCT, there was no significant difference between 2 groups in the loss of weight and body BMI. The available evidence shows that patients receiving home enteral nutrition yielded a significantly better BMI and lower decrease in body weight than those without after surgical resection of oesophageal cancer. We conclude that HEN could serve as an effective intervention for patients undergoing oesophagectomy. Moreover, the optimal time for patients receiving HEN could be 4–8 weeks after discharge. Feeding via jejunostomy and nasointestinal tube are feasible and safety approaches for HEN. Abstract : A best evidence topic was constructed according to a structured protocol.